How the Republic of Korea's Financial Structure Affects the Volatility of Four Asset Prices - Min, G. Hong (The World Bank, 1999)
April 2000 - How Korea's financial structure affects the volatility of Korea's real effective exchange rate, money market rate, government bond yields, and stock prices. Min and Park explore how Korea's financial structure affects the volatility of asset prices. Documented empirical evidence of the relationship between financial structure and financial crisis sheds light on the relationship between asset price volatility - extreme variations in prices - and financial structure. And the volatility of financial and nonfinancial asset prices provides an indirect link between an economy's financial structure and the likelihood of financial crisis. Using time-series data and a set of indicators measuring financial structure, Min and Park examine how Korea's financial structure affects the volatility of the real effective exchange rate, the money market rate, government bond yields, and stock prices. They find: · There is a stable long-term relationship between financial structure and volatility in the real effective exchange rate, the money market rate, stock prices, and the yield on government housing bonds. · Financial structure affects asset price variables asymmetrically. Some variables' volatility increases and others' diminish, suggesting that monetary policies should target different asset markets to achieve different goals. If the goal of the monetary authority is to stabilize the money market rate, for example, intervening in the banking sector is more efficient than intervening in other financial subsectors. · The higher volatility of stock prices reflects the thin stock market in Korea. · The stability of the yield on government housing bonds reflects the Korean government's policy of stabilizing the nation's housing supply by isolating the housing market from the impact of Korea's financial structure.